Assessing the Impact of Classroom Enviroment on Learning Outcomes: A Survey of Students and Teacher Perspective - Marissa Swanda Tupamahu; Vanessa Rivai (Civiliza Publishing, Indonesia., 2026)
This study investigates the impact of classroom environments on student learning outcomes from both student and teacher perspectives. Using a descriptive quantitative approach, data were collected from 150 participants, consisting of 100 students and 50 teachers in Sorong City. The questionnaire covered four main categories: physical classroom environment, social classroom environment, psychological classroom environment, and learning outcomes. Reliability testing using Cronbach’s Alpha confirmed that most categories were consistent, although the physical environment required improvement. The results revealed that while the physical environment was moderately supportive, the social and psychological aspects had stronger positive influences on student motivation, engagement, and achievement. These findings underscore the importance of enhancing classroom conditions beyond physical resources, by also fostering supportive interactions and psychological well-being. The study contributes practical insights for educators and policymakers in designing classroom environments that holistically promote academic success.